Prostaglandins, Thromboxanes and Leukotrienes in Clinical Medicine - Zipser, Robert D. (1985)
Although prostaglandin research began about 50 years ago, many of the most important advances in understanding the biochemistry, physiology and pharmacology have taken place within the past five to ten years. There is great potential for the extension of this research to the clinical practice of medicine. At this time, the most common interaction that clinicians have with the prostaglandin field is in administering nonsteroidal anti-inflammatory drugs, which function by inhibiting prostaglandins. The uses of these drugs include treating not only inflammation, but also dysmenorrhea, some renal disease, thrombotic diseases and some metabolic disorders. Prostaglandin analogs, with their potent effects on uterine contraction, are in common use in obstetrics. Other analogs, with gastric and duodenal cytoprotective effects are useful in treating peptic ulcer disease. Future benefits from prostaglandin and leukotriene research may include new therapy for inflammatory and hypersensitivity diseases such as asthma, inflammatory bowel diseases and dermatitis.